A Functional Role of the Cyclin-Dependent Kinase Inhibitor 1 (P21WAF1/CIP1) for Neuronal Preconditioning. Issue 3 (March 2013) - Mergenthaler, Philipp; Muselmann, Claudia; Sünwoldt, Juliane; Isaev, Nickolay K; Wieloch, Tadeusz; Dirnagl, Ulrich; Meisel, Andreas; Ruscher, Karsten
Hypoxic preconditioning is thought to rely on gene products regulated by hypoxia-inducible factor (HIF)-1. Here, we show that the HIF-1 target gene cyclin-dependent kinase inhibitor 1, p21 WAF1/CIP1, is essential for neuroprotection by hypoxic/aglycemic or erythropoietin preconditioning using wild-type and p21 WAF1/CIP1 -deficient neurons. Furthermore, overexpression of wild-type p21 WAF1/CIP1 or phospho-mutants significantly increased cell death after hypoxia/aglycemia. Moreover, deferoxamine-induced endogenous tolerance did not involve p21 WAF1/CIP1 expression in cortical neurons. Our data suggest that balanced expression and potentially posttranslational regulation of p21 WAF1/CIP1 is required for hypoxic preconditioning.